Penilaian Tingkat Eco-driving pada Trans Sarbagita Koridor II untuk Mendukung Konsep Transportasi Berkelanjutan di Provinsi Bali - Putu Aprilia Apsari; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2022)
Nowadays, more people choose to live in urban areas for economic, technological, sociological or political reasons. This is the cause of increasing population and population density in urban areas. The drastic increase in population can cause various problems. One of the most important problems that can be caused is traffic congestion and the increase in the resulting CO2 emissions. Urban communities have very dynamic mobility and in their mobility they prefer to use private vehicles rather than existing public transportationAlthough there has been Trans Sarbagita as a government effort to provide sustainable public transportation, not many people have taken advantage of the existence of Trans Sarbagita. As a result, Trans Sarbagita's total income is not proportional to its operational costs. In order to reduce operational costs, there are several ways that can be done, one of which is eco-driving. Eco-driving has been widely introduced as an environmentally friendly and economical way of driving that supports aspects of sustainable transportation, but not everyone practices or even knows this, including Trans Sarbagita drivers. Therefore, there is a need for an assessment of the level of eco-driving, especially on Trans Sarbagita to support the concept of sustainable transportation.The data used is a score based on the Guttman scale from the results of observations of five eco-driving indicators for 24 drivers on Trans Sarbagita Corridor II. Based on the analysis that has been carried out, the trans Sarbagita Corridor II eco-driving level is generally included in the medium category. The category level of the bus stop segment is divided into 2 categories, namely 8 bus stop segments with a high eco-driving category and 18 bus stop segments with a moderate eco-driving level. Based on the three aspects of sustainable transportation that must be met, Trans Sarbagita Corridor II is only able to meet all the criteria in the social aspect. In the economic aspect, Trans Sarbagita Corridor II is only able to meet the area accessibility criteria of the 3 existing criteria. Meanwhile, on the environmental aspect, Trans Sarbagita failed to meet the only criterion that must be met, namely the minimization of environmental pollution due to the impact of transportation. Based on the description above, from the three existing aspects, Trans Sarbagita Corridor II has not been supported by economic and environmental aspects, so it can be concluded that Trans Sarbagita Corridor II has not fully supported the concept of sustainable transportation.